2019
DOI: 10.3991/ijet.v14i06.9717
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Presenting Anomalous Data on Improving Student’s Critical Thinking Ability

Abstract: This study aim to explore the effects of presenting anomalous data on improving student’s critical thinking ability. This study is an experimental research conducting on one-group pretest-posttest design. Purposive sampling was used in this study, where one class group was used as a sample of the study, namely 36 students of senior high school at MA Hidayaturrahmah NW Menggala, North Lombok, West Nusa Tenggara, Indonesia. The data of CT ability collected by instrument refer to Ennis-Weir Critical Thinking Essa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
(13 reference statements)
1
22
0
1
Order By: Relevance
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
See 1 more Smart Citation
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
“…The problems with critical thinking skills and the difference in pre-service teachers' academic ability can be overcome by applying constructivism-based learning (Kusaeri & Aditomo, 2019;Mahanal et al, 2019;Prayogi et al, 2019;Vong & Kaewurai, 2017;Zubaidah et al, 2018). Two constructivism-based learning models believed having potential to improve pre-service teachers' critical thinking skills are the RQA and QASEE learning models.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that knowledge about university functions, skills and service attitudes of administrative staff play a very important role in increasing student satisfaction. Service has an impact on many aspects, especially creating a good academic atmosphere, because global demands expect students to not only be able to study well but develop their thinking according to the demands of the 21 st century (Prayogi, Yuanita, & Wasis, 2018;Prayogi, et. al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The number of questions as many as 8 (eight) items follow the indicator of critical thinking ability, so the maximum score is +24 and the minimum score is -8. The conversion of scores into categorized qualitative data adapted from Prayogi, et. al.…”
Section: Methodsmentioning
confidence: 99%
“…One of the factors that causes the low quality of learning is the learning process that does not encourage students to think critically. Critical thinking has become a major trend and focus in learning, even curriculum authorities in some developed countries have included the critical thinking ability in their curriculum as a learning objective and one of the essential skills in the 21 st century (Prayogi, Yuanita, & Wasis, 2017;Prayogi, et. al., 2019).…”
Section: Introductionmentioning
confidence: 99%